Zolav®: a new antibiotic for the treatment of acne [Corrigendum] - Dinant A; Boulos RA (Dove Medical Press, 2016)
Dinant A, Boulos RA. Drug Des Devel Ther. 2016;10:1235–1242.All mentions of “Zolav” throughout this paper should read “Zolav (a p-carboethoxy-tristyrylbenzene derivative)”.Read the original article